Influence of the gap size on the response of a single-degree-of-freedom vibro-impact system with two-sided constraints: Experimental tests and numerical modeling. (15th September 2021) - Stefani, Giulia; De Angelis, Maurizio; Andreaus, Ugo
Highlights: The gap width influences the experimental response of a vibro-impact SDOF system. Positive, null, and negative gaps were considered. For small negative gaps a primary resonance with left hysteresis was observed. Excessive negative gaps affect the bumpers response and not that of the mass. Secondary resonances, associated with multiple impacts, occurred for small gaps at low frequencies. Graphical abstract: Abstract: The large displacements caused by strong earthquakes in base-isolated structures (buildings, bridges, strategic facilities, equipment, ⋯ ) can excessively deform or damage the isolation system or lead to pounding with surrounding moat walls or adjacent structures, if the available seismic gap is not sufficient. The acceleration spikes caused by the impact can damage the structure itself as well as sensitive equipment housed in it. A possible mitigation measure consists in the interposition of deformable shock absorbers (bumpers). In this paper, the influence of the gap amplitude on the experimental response of a single-degree-of-freedom oscillator, excited by a harmonic base acceleration and symmetrically constrained by two unilateral deformable and dissipative bumpers, is investigated. The parametric investigation considered both positive, null, and negative gaps. Particular attention is paid to the study of the effect, on the system response, of the transition from positive to small negative gaps and of excessive negative gaps. Secondary resonances in the low frequency range, associated with the occurrence of multiple impacts, were experimentally observed for small positive gaps. Finally, the experimental results were reproduced, in a sufficiently accurate manner, using a suitable numerical model, whose parameters were identified based on the experimental data.